Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

please solve it!

Asked by 6th September 2009, 11:13 AM
Answered by Expert
Answer:

Given: m = 1/2; u = - 60 cm;

since m = - v / u;

v = - m u = 30 cm

using mirror formula

(1 / f) = (1 /  v) + (1 / u)

(1 / f) = (1 / 30) - (1 / 60)

f = 60 cm

In the second case -

m = 1/ 3;

m = - v / u;

v = - u / 3;

Again using mirror formula

(1 / f) = (1 /  v) + (1 / u)

(1 / 60) = (- 3 / u) - (1 / u)

(1 / 60) = - 4 / u

u = - 240 cm

Answered by Expert 8th September 2009, 2:25 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp